2014
DOI: 10.1111/gbb.12181
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal neuronal circuits of contextual fear conditioning

Abstract: Over the past years, numerous studies have provided a clear understanding of the neuronal circuits and mechanisms involved in the formation, expression and extinction phases of conditioned cued fear memories. Yet, despite a strong clinical interest, a detailed understanding of these memory phases for contextual fear memories is still missing. Besides the well-known role of the hippocampus in encoding contextual fear behavior, growing evidence indicates that specific regions of the medial prefrontal cortex diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(81 citation statements)
references
References 194 publications
(248 reference statements)
4
76
1
Order By: Relevance
“…In order to provide a more comprehensive analysis on the cognitive functions, more additional hippocampus-dependent tasks including the novel object recognition task and contextual fear conditioning task for associative learning are particularly needed to be employed in the future study [79][80][81][82][83][84].…”
Section: Amd3100 Reversed the Insults Of Tlementioning
confidence: 99%
“…In order to provide a more comprehensive analysis on the cognitive functions, more additional hippocampus-dependent tasks including the novel object recognition task and contextual fear conditioning task for associative learning are particularly needed to be employed in the future study [79][80][81][82][83][84].…”
Section: Amd3100 Reversed the Insults Of Tlementioning
confidence: 99%
“…Convergent evidence indicates the brain areas that are dysfunctional in PTSD patients correspond to those responsible for learned fear processing in laboratory animals (Pitman et al, 2012;Maren et al, 2013;Rozeske et al, 2015;Besnard and Sahay, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This implicates the inhibition of neuronal activity in some cortical targets in the impairment of long-term aversive memory. Neuronal tracing studies have shown that the PFC reciprocally projects to the BLA (Hu¨bner et al, 2014) and midline thalamus (Vertes and Hoover, 2008;Varela et al, 2014;Rozeske et al, 2015). Besides, the PFC can indirectly modulate hippocampus activity through its efferences to the nucleus reuniens of the midline thalamus, which directly projects to CA1 (Varela et al, 2014).…”
Section: Discussionmentioning
confidence: 99%